Analysis of the Differences in Practical Skills of Land Surveying I Based on University Admission Paths - Natsir, Taufiq; Ishak, Ishak; Yusrianti, Yusrianti (PINISI Discretion Review, 2024)
This research aims to determine: 1) Practical Skills of Land Surveying I in the SNBP Admission Path. 2) Practical Skills of Land Surveying I in the SNBT Admission Path. 3) Practical Skills of Land Surveying I in the Independent Admission Path. 4) Differences in Practical Skills of Land Surveying I Based on the SNBP, SNBT, and Independent Admission Paths. This research was conducted in the Department of Civil Engineering Education and Planning, Faculty of Engineering, State University of Makassar. This study employed a quantitative approach with a comparative design. The research sample consisted of 127 students from the Building Construction Civil Engineering Program, Class of 2023, Faculty of Engineering, State University of Makassar, selected through random sampling. Data collection was conducted using observation sheets, descriptive data analysis, categorization analysis, as well as hypothesis testing, including tests of normality, homogeneity, and ANOVA. The results of the study showed that: 1) Practical Skills of Land Surveying I in the SNBP admission path had a high category, with a percentage of 41.94%. 2) Practical Skills of Land Surveying I in the SNBT admission path also had a high category, with a percentage of 44.90%. 3) Practical Skills of Land Surveying I in the Independent admission path had a high category, with a percentage of 53.19%. 4) Based on the analysis, the obtained significance value (sig) was 0.012 < α (0.05), indicating that the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. This means that there is a significant difference in the Practical Skills of Land Surveying I based on the University Admission Paths for the Building Construction Civil Engineering Program, Class of 2023, at State University of Makassar.